Expert testimony on the psychology of eyewitness identification - Cutler, Brian L. (New York ; Oxford : Oxford University Press, 2009)
Compelling though it may be in a criminal trial, two decades of research have shown that eyewitnesses are sometimes wrong, even when they are highly confident. This book brings together researchers and practising attorneys to provide overviews and critiques of key topics in eyewitness testimony.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Eyewitness identification -- United States -- Psychological aspects; Forensic psychology -- United States